Self-Medication Among Pregnant Women: Prevalence and Associated Factors - Pereira, Gabriela; Surita, Fernanda Garanhani; Ferracini, Amanda Canato; Madeira, Cinthia de Souza; Oliveira, Letícia Silva; Mazzola, Priscila Gava (Frontiers in Pharmacology, 2021)
Objectives: The pregnancy period, with its peculiarities and specific symptoms that may or may not be physiological, can lead to medication use through prescription or even self-medication. This study aimed to assess self-medication practices among pregnant women, the most used medications, symptoms reported, and factors associated with this practice. Methods: This was a cross-sectional study conducted with pregnant women with an antenatal care (ANC) appointment in a tertiary teaching hospital referral in women’s health. From April 2019 to February 2020, 297 pregnant women were interviewed. Self-medication was considered as the use of any medicine (including medicinal plants (MPs), herbal products, and vitamins) without a medical or dental prescription. The period considered to assess self-medication practice was the last 60 days prior to the study interview. Results: Among the 297 women interviewed, 107 (36.0%) had practiced self-medication in the previous 60 days. Acetaminophen was the most used medication, and headache was the most frequent symptom reported by self-medicated pregnant women. Pregnant women with high-school (73 (68.2%) (OR = 2.52; 95% CI 1.17–5.43; p = 0.018)) or university-level (23 (21.5%) (OR = 2.82; 95% CI 1.15–6.94; p = 0.024)) education had a higher risk of practicing self-medication when compared to women with lower education. Women in the first gestational trimester (35 (32.7%) (OR = 3.61; 95% CI 1.64–7.96; p = 0.002)) and with two or more pregnancies (87 (81.2%) (OR = 1.96; 95% CI 1.07–3.60; p = 0.029)) were more likely to practice self-medication than pregnant women in the second or third gestational trimester and in the first pregnancy, respectively. Conclusion: Self-medication was practiced by a considerable proportion of our sample, with the majority being OTC drugs. The factors associated with self-medication can help to improve prevention strategies regarding self-medication during pregnancy.